2-In-1 smart panels: Embedding phased array patch antennas within satellite structures. (October 2020) - Platero, Valorie; Ferguson, Philip; Jayaraman, Raghavan; Isleifson, Dustin
Abstract: The increasing commercialization of space missions call for versatile subsystems that make efficient use of limited spacecraft volumes. Smart panel technology that provides both mechanical and electrical functionality is a beneficial solution to spacecraft miniaturization. Combining different subsystems that are usually developed independently of each other is an innovative approach to space system design. Embedding antennas within satellite structural components reduces the overhead required for integrating numerous systems and maximizes space for the payload and other critical instruments. Microstrip patch antennas provide a low profile, light weight, small-dimension and easily manufactured solution to small satellite communication. The phased array functionality of the antenna enables dynamic beamforming for maximum versatility. In this paper, we evaluate the feasibility of an embedded phased array microstrip patch antenna with a hybrid composite structural panel comprised of carbon fiber reinforced epoxy composite (CFC), Polyethylene fiber reinforcedpolyethylene composite (PFC) (HDPE), and aluminium, with SU-8 as the antenna substrate. The embedded antenna panels are designed to be adaptable for any function and size required by the end user. We present the design of the smart panel antenna modelled using electromagnetic simulation software. The CFC and PFC materials are modelled with approximations of their electrical properties derived from experimental S-parameter and impedance measurements. The simulated antenna's radiation performance such as half power beamwidth, efficiency and gain are evaluated. The performance characteristics of the simulated antenna design are used to evaluate its application and feasibility in systems integration, and different uses in case studies including radar mapping spacecraft, satellite constellations, and CubeSats. Highlights: Multifunctional structures utilize passive spacecraft elements and maximizes useable volume. Embedding antennas reduce risk of collision and eliminates need for deployable structures. SU-8 photoresist as a substrate and composite panel as a ground plane. 3 x 3 planar patch antenna array with directional peak gain of 12 dB. Phased array steering range of −50°–50° in x-direction and −46°–46° in y-direction.